A data envelopment analysis approach for evaluating high-speed freight transportation efficiency - Paulo Chenrrim; Susana Relvas (Transportation Research Interdisciplinary Perspectives)
Rail transport has a high potential for the development of countries and their economies and is aligned with the policies associated with the energy transition. This study addresses the need for support tools to assess the potential of rail freight transport on high-speed lines. Our motivation stems from the fact that this is still an under-explored topic and the importance it can have for the efficiency of the transport and logistics systems. The methodology in this article is based on the use of Data Envelopment Analysis (DEA) through the BCC (Banker, Charnes, and Cooper) model and VRS (Variable Returns Scale) approach with an input orientation and the global Malmquist Productivity Index (MPI) to assess the efficiency of the freight transport option on high-speed networks, with the aim of contributing to more informed decision-making.The proposed methodology was applied to the Portuguese context. We found that increasing train speed can increase the overall efficiency score of the Decision-Making Units (DMUs) by 21 percentage points compared to a scenario without this input, thus boosting the technical efficiency of freight railway companies. This result, while cautious, highlights the importance of considering various inputs to optimise the performance of these companies.